2018
DOI: 10.1186/s12978-018-0468-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of sperm, egg and embryo donors and recipients towards genetic information and screening of donors

Abstract: BackgroundGamete and embryo donors undergo genetic screening procedures in order to maximise the health of donor-conceived offspring. In the era of genomic medicine, expanded genetic screening may be offered to donors for the purpose of avoiding transmission of harmful genetic mutations. The objective of this study was to explore the attitudes of donors and recipients toward the expanded genetic screening of donors.MethodsQualitative interview study with thematic analysis, undertaken in a tertiary fertility ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…Our values are higher than previous studies that only considered the findings of carrier screening. These results support the need for specialized pre-test and post-test counseling to deal with these findings and the psychological burden to the candidates ( Amor et al ., 2018 ).…”
Section: Discussionsupporting
confidence: 76%
“…Our values are higher than previous studies that only considered the findings of carrier screening. These results support the need for specialized pre-test and post-test counseling to deal with these findings and the psychological burden to the candidates ( Amor et al ., 2018 ).…”
Section: Discussionsupporting
confidence: 76%
“…karyotyping or carrier status) ( Dondorp et al , 2014 ; European Directorate for the Quality of Medicines & HealthCare (EDQM), 2019 ). Amor et al (2018) showed that donors (as well as recipients) are hesitant about the process of genetic screening and there are concerns about how this information may be used, and the ethics of selectivity.…”
Section: Recommendations For Information Provision and Support For Do...mentioning
confidence: 99%
“…At present, sperm banks and clinics use very different panels, some containing hundreds of diseases including diseases whose detection may have a direct impact on the donors' future health and/ or reproduction (Pennings, 2020). The attitude of the donors in this study differs considerably from that of Australian donors who were much more concerned about increased genetic testing and who, if tested, did not want to know the results (Amor et al, 2018). Only around 20% in the current study seemed to want some degree of control over the information flow of the results of the testing.…”
Section: Discussionmentioning
confidence: 90%
“…There is a lack of empirical studies on the experiences of and attitudes of donors towards expanded carrier screening (Amor et al, 2018). Oocyte donors in a Spanish clinic were surprised by the information on testing and the possibility of being carriers (Abuli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%